Підходи до формування та структуризації потенціалу підприємства - Рижаков, Д. А. (Ways to Improve Construction Efficiency, 2012)
The approaches to capacity-building enterprises, analyzes options for structuring and proposed structure of the potential at the interface between companies with market environment and strategic development of the company.